2009
DOI: 10.4081/ijas.2009.491
|View full text |Cite
|
Sign up to set email alerts
|

Some new aspects of nutrition, health conditions and fertility of intensively reared dairy cows

Abstract: Speaking in terms of the general relationship between nutrition and reproduction, many different aspects are more or less involved depending on geographical areas, species, production systems, technological levels etc. There are deficiency conditions: energy, proteins, vitamins and minerals; but also some excesses (namely protein and few minerals) or toxic substances such as micotoxins or plant compounds (i.e. phyto-oestrogens). Their relevance is different in the intensive systems for better feeds and relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 133 publications
(158 reference statements)
1
63
2
Order By: Relevance
“…It is widely accepted that the transition period is critical for health disorders and that high milk yield can be responsible for higher disease susceptibility (Bertoni et al, 2009). Uribe et al (1995) demonstrated a high and inverse correlation between milk yield and hypocalcaemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that the transition period is critical for health disorders and that high milk yield can be responsible for higher disease susceptibility (Bertoni et al, 2009). Uribe et al (1995) demonstrated a high and inverse correlation between milk yield and hypocalcaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The function of the digestive tract organs determines the metabolic balance of the whole organism of a high yielding cow (Ingvarsten et al, 2003;Beever, 2006). The homeostasis disturbance during this period is crucial for the performance of the dairy animals in the current as well as in the next lactations (Bertoni et al, 2009;Jóźwik et al, 2010b). The intensive energy turnover, under conditions of limited body reserves, causes high yielding cows to be more susceptible to numerous pathogenic factors, especially in early lactation (Ingvarsten et al, 2003;Litwińczuk et al, 2011).…”
mentioning
confidence: 99%
“…Changes in the direction and magnitude of various pathways of long-chain fatty acid (LCFA), glucose and amino acid metabolism, as cows go from late pregnancy through lactation have been well-described during the past 20 years (reviewed recently by Drackley et al, 2006). Besides the well-established knowledge, more recent data have underscored the link between negative energy balance (NEB), oxidative stress and inflammation (Bertoni et al, 2009). This period of the lactation cycle clearly is one where inter-tissue coordination must be tightly regulated so the animal can make a smooth transition into lactation, that is, free of metabolic or infectious disease.…”
Section: Linking Cattle Genome To Ruminant Metabolismmentioning
confidence: 99%
“…The biological consequence of downregulation of the complement system would be a reduction in inflammatory-like responses after parturition compared to control cows. The inflammatory-like conditions typical in peripartal cows have detrimental influence on performance (Bertoni et al, 2009); thus, the reduction of the complement system should have prevented or reduced the postpartal inflammatory-like response. It appears from the above studies that 'nutritional stress' and 'metabolic stress' seem to be characterized by widely different responses at the level of liver and likely encompass alterations in peripheral signals including cytokines, metabolites and/or hormones.…”
Section: Linking Cattle Genome To Ruminant Metabolismmentioning
confidence: 99%